2019
DOI: 10.25170/jm.v15i2.470
|View full text |Cite
|
Sign up to set email alerts
|

Could Satisfaction on the Airline’s Service Quality (Airqual) Make Lion Air’s Customers Trust and Become Loyal to the Airline Company?

Abstract: The Indonesian public interest in using the service flights as their means of transportation is remarkably growing according to Indonesia Investment data in 2017. People tend to use service flights because of Indonesia's unique geographical nature and airline tickets becomes increasingly affordable as the growth low-cost carrier. The purpose of this research is to investigate the role of customer satisfaction toward the airline's service quality (AIRQUAL) in effecting trust and loyalty. The study was directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Passenger satisfaction was also the mediation of the influence between the service quality to customer loyalty, customers whose customer loyalty had passenger satisfaction with the quality provided by Lion Air airline. This research was also supported by (Lembana & Valucy, 2019), who got results where research showed that Satisfaction made passengers who were satisfied with the quality of airline service loyal to Lion Air in addition to the results of research conducted by Namusaka (2013) obtaining results where passenger satisfaction as a mediation variable also significantly affected customer loyalty.…”
Section: H7: Service Quality Has a Positive Influence On Customer Loyalty Mediated By Passenger Satisfactionsupporting
confidence: 56%
“…Passenger satisfaction was also the mediation of the influence between the service quality to customer loyalty, customers whose customer loyalty had passenger satisfaction with the quality provided by Lion Air airline. This research was also supported by (Lembana & Valucy, 2019), who got results where research showed that Satisfaction made passengers who were satisfied with the quality of airline service loyal to Lion Air in addition to the results of research conducted by Namusaka (2013) obtaining results where passenger satisfaction as a mediation variable also significantly affected customer loyalty.…”
Section: H7: Service Quality Has a Positive Influence On Customer Loyalty Mediated By Passenger Satisfactionsupporting
confidence: 56%
“…Today's aviation business is intensely competitive (Chonsalasin, Jomnonkwao, & Ratanavaraha, 2020;Wang & Chaipoopirutana, 2015). Several previous studies have focused on the greater competitiveness of low-cost airlines (Chayomchai, et al, 2021; Gures, Inan, & Arslan, 2018; Lee, et al, 2018;Lembana & Valucy, 2018; Yunus, Bojei, & Rashid, 2013). However, competitive advantage can be gained from other factors such as passenger attitude factor (like consumer satisfaction or passenger loyalty) or airline crew factor.…”
Section: Introductionmentioning
confidence: 99%
“…Not only that, Lion Air is on the top place of the complaint category list in 2014 (Lembana & Valucy, 2018). Lion Air is known as the most often flight delayed and has the unsatisfying services (Praditya & Astuti, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the well-known airline companies in Indonesia, Lion Air has many competitors (Lembana & Valucy, 2018). Thus, understanding the factors of customer repurchase intention is necessary to survive and grow in the middle of competitive service sector is important (Saleem, Zahra, & Yaseen, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation